geographical area as the stage for the individual and social development in preschool children (Revista Electrónica REDINE, 2018)
In the following essay geographical space is seen as an important curricular element in the social sciences and the challenge of teaching to the perception of knowledge and meanings of the reality that surrounds being. In the same importance it is given to the construction of learning by the child / girl Preschool level in relation to the basic concepts of geography. It is based on documentary research methodology. the information is analyzed, recognizing the importance of creativity and imagination of children, proceedings are carried out in the geographical learning , emphasizing the natural through educational social practices for the welfare of the individual and the collective ; considering also that the teaching is integral and must be clearly oriented to the discipline to be studied , case study: early childhood education, preschool and geographical science.
Keywords: geographical space; social sciences; Preschool Stage